MENITI JEJAK RASULULLAH: MENOLONG UMAT DENGAN MEMBERDAYAKAN USAHA MIKRO KELUARGA IBU SOPIAH - Dzaljad, Rifma Ghulam; Putri , Fatihah Shasikirana; Gumilar , Ghaniyya Illyani; Hamidah, Nasywa Atheera Fauziah (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Empowerment is an activity that aims to improve and develop the capacity, quality and welfare of their lives. This article discusses and implements the teachings of Surah Al-Maun in the Muhammadiyah course at Muhammadiyah University, Prof. Dr Hamka, South Jakarta. The aim is to provide learning to the community through humanitarian empowerment. The approach used is an economic approach, namely by developing the economy of underprivileged families. So that it can increase the family's income and quality of life. This approach can be taken if the family has an economic business or the potential to manage productive economic activities independently. The methods used in this empowerment are observation, discussion and practice. This economic empowerment activity was carried out in the Mangga Ulir RPTRA Area, Kebayoran Lama District, South Jakarta City on March 29 2024.